Pengelolaan Pendanaan Kegiatan Pemberian Makanan Tambahan Balita pada Pelayanan Posyandu KIA Desa Kalidesel - Alissa Sita Pertiwi (Yayasan Pendidikan Medika Indonesia, 2021)
Financial management of Posyandu is essential, including supplementary feeding for the under-5 child. The problems that could occur were lack of financial management skills, as well as Posyandu cadres' limited knowledge. This study aims to explore the fund management for supplementary feeding activities at Kalidesel Village in 2018-2020. This study used a qualitative method with a case study approach. The location of the study was Kalidesel Village, Watumalang, Wonosobo. Research results obtained were the Posyandu staff could utilize 3 different sources of funds flexibly. In addition, the implementation of the supplementary feeding in 2 different Posyandu resulted in differences in the division of cadre tasks and the type of supplementary food provided. The reporting activity was not carried out by the midwive and cadres. Posyandu managers, both midwives and cadres, should receive training in managing, recording and reporting program funds. This is because fund management is very important to maintain the continuity and sustainability of a health program.